Lietuvos politinių ir diplomatinių santykių su Prancūzija užmezgimas (1918-1920): nepasitikėjimo mainai - Bukaitė, Vilma (Lietuvos istorijos studijos, 2011)
In 1918, the Lithuanian state was re-established referring to the principle of self-determination of nations. Hence, the first Lithuanian government expected to receive the due support and recognition from the most powerful winners of World War I, including France. However, one of the most influential architects of 'New Europe', the French Prime Minister Georges Clemenceau, conceived this new Baltic state as a potential territory of democratic Russia, which the French allies seeked to restore, and later on of Poland. According to this politician who presided at the Paris Peace Conference, Lithuania was meant to become a federal part of one of these states. His rather skeptical attitude towards the statehood of Lithuania emanated from doubts as to whether a new state would be able to retain its political autonomy while bordering with Germany and the Soviet Russia; such opinion also resulted from aspirations to consolidate a 'cordon sanitaire' between the two potential enemies of France. Another important factor was the sense of mistrust with regard to the state that had been created on the Germany's occupied territory.Members of the Lithuanian delegation headed by the minister of foreign affairs Augustinas Voldemaras were present at the Paris Peace Conference and intermediated between their own and French governments, but could not dissipate the atmosphere of mistrust in the state being represented. Another intermediary, the French military mission headed by a lieutenant-colonel Constantin Reboul, was the first unit representing the Entente in Lithuania. C. Reboul's proposals to enter into commercial relations and send some of the military training instructors as well as munition to the Lithuanian armed forces did not receive the expected support in France. The advantages offered under the strengthened French cultural influence, i.e. training instructors at military school, charity of vaccination against zymotic diseases and some favourable political proposals, were all outweighed by the sense of mistrust expressed by the Lithuanian government with regard to the mission which initially had been made welcome. Such an obvious lack of confidence resulted from C. Reboul's tireless efforts to bring Lithuania and Poland together, with the aim at forming a common federal state. The mission encouraged the French government to concede the Klaipėda Region (Memel Territory) to Lithuania. However, it was France that from 20 January 1920 became in charge of the Region as the administering state. The emerged obstacle in the way of annexing the seaboard areas with the Port of Klaipėda resulted in the Lithuanian government's dissatisfaction, which in turn raised new difficulties for a benevolent cooperation with both the French government and its respective mission. The Lithuanian government deliberately put economic and political pressure on the Klaipėda Region administration governed by the General Dominique Joseph Odry, with the purpose to take control over the Region as a matter of urgency.The unfavourable attitude of the Lithuanian government and the public towards the French policy was anchored by the demarcation line which was defined at the time when Poland laid its claims to the southern and eastern territories of Lithuania. The second demarcation line, determined by the Marshal Ferdinand Foch, was met in an especially adverse manner. The demarcation lines, which were supposed to divide the territories of the states temporarily at war, eventually led to the long-lasting issue of Vilnius Region. The French government provided the necessary financial aid and trainings, thus strengthening the Polish Army, but did not preclude its ally from advancing on the Lithuanian territory. Therefore, the Lithuanians considered the French government as a culprit of the Polish military aggression. The public discontent reached its apogee on 17 August 1919 when demonstrations and meetings were held against the French policy.The Cabinet of Alexandre Millerand, in function from 20 January 1920, was less tolerant towards the Polish political pressure on Lithuania. His political decisions were an ice-breaking point of the bilateral relations, though short in duration and fragile. On May 11, the French government de facto recognized the Lithuanian government. Such diplomatic gesture was met rather unresponsively, being cast into shadow by other political events. After the areas of interest in Europe had been divided among the great powers, Great Britain became prevalent in the Baltic states. Improvement of the relations was then interrupted by the coup of Lucjan Żeligowski in October 1920. The French military mission provided support to the participants of the coup, since Georges Leygues' government was in favour of Poland, but such an attitude provoked a new major wave of mistrust with regard to France. In summer 1920, Lithuania was no longer conceived by the French politicians as the land of nowhere, quoting Alfred Jarry's "Ubu Roi", although only a few among them could have been truly in sympathy with this new state.